THE IMPLEMENTATION OF PROJECT BASED LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES IN STUDY ABOUT "PENGANTAR PANCASILA" - Deklay Nainggolan; Hans Frans Pontororing; Dominicus Tinus (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2021)
This research was conducted to improve learning result of Students on semester 1 when study about “Pengantar Pancasila” by applying the Project Based Learning (PjBL) model. Data obtained in this study were obtained from observation, document study, test. Data analysis technique used is descriptive quantitative and qualitative with 41 people as sample from Guidance and Conseling Department, Faculty of Education, UNIMA. This study is a classroom action research (PTK) consisting of two cycles. Each cycle consists of two meetings, each of which consists of action planning, action implementation, observation and reflection and 1 evaluation meeting. The results showed that the application of learning model of Project Based Learning (PjBL) can improve student learning outcomes. At the pre cycle percentage of student learning 29% and then increased in the first cycle as much as 46% and increased again to 100% in cycle II.